2015
DOI: 10.1093/ijnp/pyu002
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 (Zinc Receptor) Knockout Mice Exhibit Depression-Like Behavior and CREB/BDNF Down-Regulation in the Hippocampus

Abstract: Background:Zinc may act as a neurotransmitter in the central nervous system by activation of the GPR39 metabotropic receptors.Methods:In the present study, we investigated whether GPR39 knockout would cause depressive-like and/or anxiety-like behavior, as measured by the forced swim test, tail suspension test, and light/dark test. We also investigated whether lack of GPR39 would change levels of cAMP response element-binding protein (CREB),brain-derived neurotrophic factor (BDNF) and tropomyosin related kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 49 publications
0
49
1
2
Order By: Relevance
“…6). Moreover, we found that mice lacking the GPR39 gene, which show 'depressive-like' behavior (Młyniec et al, 2015a), have decreased tryptophan and tyrosine concentrations in the hippocampus, but not in the frontal cortex. We did not observe any changes in glutamate levels between the GPR39 KO and WT groups, neither in the hippocampus nor in the frontal cortex.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…6). Moreover, we found that mice lacking the GPR39 gene, which show 'depressive-like' behavior (Młyniec et al, 2015a), have decreased tryptophan and tyrosine concentrations in the hippocampus, but not in the frontal cortex. We did not observe any changes in glutamate levels between the GPR39 KO and WT groups, neither in the hippocampus nor in the frontal cortex.…”
Section: Discussionmentioning
confidence: 84%
“…This could be a potential mechanism linking GPR39 with physiological disturbances observed in depression. In our previous study we showed a decreased CREB and BDNF levels in the hippocampus of GPR39 knockout mice, indicating a possible role of GPR39 receptor in regulation of hippocampal CREB/BDNF pathway that is also important in antidepressant response and synaptic plasticity (Młyniec et al, 2015a). A study by Besser et al (2009) provided evidence that synaptically released zinc ions activate the postsynaptic zinc receptor in the CA3 region of the hippocampus, which plays a pivotal role in mood disorders.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Western Blot was performed as described previously [29]. The hippocampus tissues from mice were homogenized using RIPA (20mgorganizationwith 200 μl RIPA).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies have linked GPR39 with metabolism including two studies of GPR39 knockout mice, one where body weight and food intake were reported to be normal (25), while the other noted higher body weight and fat composition with no change in food intake (26). A report has also linked GPR39 loss with impaired insulin secretion (27), yet synthetic agonists of GPR39 fail to drive insulin secretion (28), and still others associate GPR39 loss with nervous system symptoms such as seizures (29) and depressionlike behavior (30). GPR39 has also been proposed to function as a Zn 2+ receptor (14).…”
Section: Discussionmentioning
confidence: 99%